JAK-STAT in Early Hematopoiesis and Leukemia - Fasouli, Eirini Sofia; Katsantoni, Eleni (Frontiers in Cell and Developmental Biology, 2021)
Hematopoietic stem cells (HSCs) produce all the terminally differentiated blood cells and are controlled by extracellular signals from the microenvironment, the bone marrow niche, as well as intrinsic cell signals. Intrinsic signals include the tightly controlled action of signaling pathways, as the Janus Kinase-Signal Transducer and Activator of Transcription (JAK-STAT) pathway. Activation of JAK-STAT leads to phosphorylation of members of the STAT family to regulate proliferation, survival, and self-renewal of HSCs. Mutations in components of the JAK-STAT pathway are linked with defects in HSCs and hematologic malignancies. Accumulating mutations in HSCs and aging contribute to leukemia transformation. Here an overview of hematopoiesis, and the role of the JAK-STAT pathway in HSCs and in the promotion of leukemic transformation is presented. Therapeutic targeting of JAK-STAT and clinical implications of the existing research findings are also discussed.